PP73 Cytotoxic Potential of Doxorubicin and Amaryllidaceae Alkaloids in an In Vitro Model of Gastric Cancer - Sierra, Stefany; TRUJILLO CHACON, LINA MARCELA; OSORIO DURANGO, EDISON JAVIER (Revista Productos Naturales, 2025)
Cancer is one of the leading causes of death worldwide, accounting for approximately 10 million deaths in 2022 [1]. Among the most common types of cancer globally, gastric cancer ranks as the fifth most prevalent. However, in Colombia, it stands out as the leading type of cancer in mortality, with approximately 57 thousand deaths in 2022 [2]. Despite significant advances in understanding the disease and developing treatments, cancer continues to be a challenge for the global scientific and medical community. Currently, various treatment alternatives are employed, among which chemotherapy is one of the fundamental pillars [3].